Making a difference in the real world. User-centred impact evaluation of an eight-country, community-based early childhood programme. (June 2022) - Lake, G.; Urban, M.; Giblin, F.; French, G.; Farrell, T.
Abstract: This paper presents a unique approach to the Impact Evaluation of a project that focused on low-threshold intergenerational play-based interactions in order to support young children from marginalised communities in eight European countries. The approach builds upon the work of Fetterman's Empowerment Evaluation and Patton's Utilization Focused Evaluation and brings them together to form an adapted model of evaluation. We outline in this paper how these two well developed methods of evaluation have been applied to a real world context, that is, the impact evaluation of a complex international project. Our approach highlights the complexities of differing contexts and allows for surprising and unintended consequences to emerge. It results, through double loop learning, a type of feedback loop with the internal stakeholders and implementers that is useful to the project coordination team, with a view to further upscaling of the initiative. Recommendations for policy at local, national and European Union levels were provided to the project and potential external users. However, the predominant feedback was provided at two crucial points along the way; during a stakeholder mapping exercise and during the further development of monitoring data tools. Highlights: Impact Evaluation of a project that focused on low-threshold intergenerational play-based interactionsin eight European countries. The approach builds upon the work of Fetterman's Empowerment Evaluation and Patton's Utilisation Focused Evaluation . It highlights the complexities of differing contexts and allows for surprising and unintended consequences to emerge. A feedback loop with the internal stakeholders and implementers that is useful to the project coordination team. Local level reflection has allowed for more general and far reaching Europe-wide principles to be drawn up.